Integrasi Perspektif Gender dalam Pembelajaran Al-Qur'an Hadis: Telaah Teoretis dan Pengembangan Model IGPAH - Ais Isti'ana; Rouf Tamim (WISE Pendidikan Indonesia, 2026)
Al-Qur’an Hadith learning occupies a strategic position in shaping students’ religious understanding while simultaneously instilling the values of social justice. However, studies in Islamic education indicate that gender bias may emerge through curricula, teaching materials, classroom language, role distribution, and learning assessment. This article aims to reconstruct the integration of a gender perspective in Al-Qur’an Hadith learning and to formulate the conceptual IGPAH model. This study employed a qualitative approach using a library research design based on literature synthesis. Data were obtained from the Qur’an, hadith, exegetical works, authoritative books, journal articles, and educational documents relevant to gender, Islamic education, gender-responsive pedagogy, and Al-Qur’an Hadith learning. The data were analyzed through content analysis involving data reduction, thematic categorization, critical interpretation, source triangulation, and conceptual synthesis. The findings reveal that gender equality has a strong theological foundation in the Qur’an through the principles of human equality, spiritual equality, equal opportunities for righteous deeds, and social partnership between men and women. The study also confirms that gender integration in Al-Qur’an Hadith learning should be implemented across the dimensions of lesson planning, instructional practice, assessment, and social transformation. The novelty of this article lies in the formulation of the IGPAH Model, which integrates theological, pedagogical, evaluative, and transformative dimensions as a framework for developing Al-Qur’an Hadith learning that is inclusive, humanistic, and justice-oriented.